1993
DOI: 10.1177/036354659302100622
|View full text |Cite
|
Sign up to set email alerts
|

The biomechanics of interference screw fixation of patellar tendon anterior cruciate ligament grafts

Abstract: Twenty-seven paired human cadaveric knee specimens were used to determine the effect of surgical technique and various interference screw parameters on the pullout strength of patellar tendon femoral bone blocks. The study compared the fixation strength of endoscopically inserted and conventional "rear-entry" screws of different diameters and lengths. In all tests the most frequent mode of failure was bone block pullout from the interference screw. There was no significant difference in fixation strength betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
81
2

Year Published

1994
1994
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 135 publications
(86 citation statements)
references
References 19 publications
3
81
2
Order By: Relevance
“…(695 N). Brown et al [1] reported that insertion torque is a weak predictor of failure load (R 2 = 0.45, P < 0.05). Based on their linear correlation, a mean insertion torque of 1 ft.-lb.…”
Section: Discussionmentioning
confidence: 99%
“…(695 N). Brown et al [1] reported that insertion torque is a weak predictor of failure load (R 2 = 0.45, P < 0.05). Based on their linear correlation, a mean insertion torque of 1 ft.-lb.…”
Section: Discussionmentioning
confidence: 99%
“…3 The Ligament Plate® (Solco Biomedical, Seoul, Korea) Fig. 2 The implants are from left to right: EndoButton®, TransFix®, BioScrew®, and Ligament Plate® ful early rehabilitation, fixation strength of the graft is the most important factor [3,6,18].…”
Section: Discussionmentioning
confidence: 99%
“…The grafts most commonly used are the BPTB and hamstring tendon. With the technical improvement of the femoral fixation devices the use of hamstring tendons in ACL reconstruction is on the rise [6]. In this study, the Ligament Plate® (Solco Biomedical, Seoul, Korea) was developed as a femoral fixation device that can provide adequate early fixation strength, and the usefulness of the Ligament Plate® was evaluated through biomechanical comparative studies with other fixation devices.…”
Section: Introductionmentioning
confidence: 99%
“…The surgical reconstruction of the anterior cruciate ligament with Bone-Patellar tendon-Bone autograft represents an attempt to re-establish knee kinematics. It has the added advantage of bone to bone healing and it does not sacrifice the knee stabilizers [11] .Various factors affect the pullout strength of the graft: bone block size, quality of bone, gap between bone block and tunnel, screw diameter and length and the angle between screw and bone block (parallel or divergent) [30][31][32][33][34][35][36] . Parallel placement of the screw with respect to femoral and tibial tunnel is desired as it is one of the factors which affect the pullout strength of the graft [32] .…”
Section: Introductionmentioning
confidence: 99%